Kepastian Hukum Nominee Agreement Kepemilikan Saham Perseroan Terbatas - Lucky Suryo Wicaksono (Fakultas Hukum Universitas Islam Indonesia, 2016)
This research discusses the establishment of Nomine Agreement especially in share ownership of Limited Company as well as the position of Nomine Agreement in Indonesian legal system. This was a normative research. The legal references were collected by conducting library research and document study. The findings show that first, the establishment of nominee agreement practically can be categorized into direct and indirect establishment of nominee agreement. Second, the existence of nominee agreement in the legal system in Indonesia has actually been prohibited in Article 33 point (1) and (2) of Law of Capital Investment. The fact that there is no strict prohibition in the Law of Limited Company concerning nominee shareholder prohibition has made nominee agreement develop well by establishing indirect nominee agreement and it is difficult to notice and prove such agreement.